Cyberchondria among information technology professionals of Bhubaneswar by using cyberchondria severity scale (CSS-15) - Dharmashree Satyarup; Sailaja Panda; Ramesh Nagarajappa; Upasana Mohapatra (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. Internet can act as an excellent resource for gaining valuable health related information. However, excessive online research and investigation about health-related issues may impose a negative impact. The term cyberchondria is used to describe a clinical condition in which frequent internet searches for health-related information leads to exaggerated anxieties about physical well-being. Objectives. To determine the prevalence of cyberchondria and associated factors among the information technology professionals of Bhubaneswar in India. Materials and methods. A cross-sectional study was carried out among 243 software professionals in Bhubaneswar using a previously validated Cyberchondria Severity Scale (CSS-15) questionnaire. Descriptive statistics in terms of number, percentage, mean and standard deviation were presented. Independent t-test and one-way analysis of variance was applied to compare the cyberchondria score between two and more than two independent variables respectively. Results. From 243 individuals 130 (53.5%) were males and 113 (46.5%) were females with mean age 29.82±6.67 years. The prevalence of cyberchondria severity was found to be 46.5%. The mean cyberchondria score of all study subjects was 43.80±10.62. It was significantly higher among those who spend more than 1 hour in the internet during night, feel fear and anxiety in visiting the doctor or dentist, interested in gaining the health-related information from other resources and agreed that gaining health related information has increased after COVID-19 pandemic (p˂0.05). Conclusion. Cyberchondria is a growing issue with regard to mental health in developing countries and has the ability to cause anxiety and distress. Appropriate actions must be taken to prevent it on a societal level.